Horizontal ramping rate framework to quantify hydropeaking stranding risk for fish. (5th December 2022) - Le Coarer, Yann; Lizée, Marie‐Hélène; Beche, Leah; Logez, Maxime
Abstract: Hydropeaking due to hydropower production can have negative impacts on aquatic fauna. One of the mechanisms for causing impacts on fish and aquatic macroinvertebrates is linked to the rapid dewatering of habitats, which can result in stranding or trapping. The magnitude of these impacts depends both on the characteristics of the flow variations and of the river morphology, as well as biological parameters (species, behavior, etc). When discharge is rapidly reduced, the risk of impacts on fishes (and notably the risk of fish stranding in dewatered zones along the riverbank) is frequently assessed by calculations of vertical ramping velocity among other methods. However, to assess fish stranding risks, the lateral ramping velocity calculated as a horizontal ramping rate (HRR) appears to be a more relevant indicator as it directly measures shoreline drawdown rates. HRR has the advantage of integrating river morphology, but it remains challenging to calculate HRRs in complex situations such as braided rivers. Using hydraulic simulations of the Durance, a gravel bed braided river, we have developed an innovative approach for HRR calculation. Considering two simulated flows, the algorithms for the calculations require partitioning the finite elements into wet and drying meshes. To recommend rates of lowering discharges during hydropeaking events, further studies are required to evaluate more precisely HRR limits for fish stranding regarding biotic and abiotic parameters: species, sizes, nychthemeral cycles, temperature, substrate, and so forth.